2002
DOI: 10.1007/bf02976606
|View full text |Cite
|
Sign up to set email alerts
|

Costunolide induces differentiation of human leukemia HL-60 cells

Abstract: Costunolide has been reported to be a cytotoxic and chemopreventive agent. This work investigated the mechanism of the antiproliferative effect of costunolide and determined that it induced differentiation of the human leukemia cell line HL-60. Costunolide exhibited a potent antiproliferative activity against HL-60 cells. It was also found to be a potent inducer of differentiation in human leukemia derived HL-60 cells through the examination of differentiation markers, as assessed by the reduction of nitroblue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Costunolide markedly increased the degree of HL-60 leukemia cell differentiation when simultaneously combined with 5 nM 1,25-dihydroxyvitamin D3 (1,25-(OH)2D3). The results indicate that PKC, PI3-K, ERK and NF-jB may be involved in 1,25-(OH)2D3-mediated cell differentiation enhanced by costunolide (Choi et al, 2002b;Kim et al, 2002).…”
Section: Antitumor and Cytotoxicmentioning
confidence: 86%
“…Costunolide markedly increased the degree of HL-60 leukemia cell differentiation when simultaneously combined with 5 nM 1,25-dihydroxyvitamin D3 (1,25-(OH)2D3). The results indicate that PKC, PI3-K, ERK and NF-jB may be involved in 1,25-(OH)2D3-mediated cell differentiation enhanced by costunolide (Choi et al, 2002b;Kim et al, 2002).…”
Section: Antitumor and Cytotoxicmentioning
confidence: 86%
“…It also reported that, costunolide is involved to inhibit the expression of inducible nitric oxide synthase (De Marino et al, 2005;Fukuda et al, 2001;Matsuda et al, 2000;Park et al, 1996) and the DNA-binding activity of NF-κB (Castro et al, 2000;Koo et al, 2001;Stefani et al, 2006) and has potential as natural herbicide (Macias et al, 1999). Furthermore, costunolide potentiated 1,25-(OH)2D3-induced differentiation in HL-60 promyelocytic leukemia cells (Choi et al, 2002b;Kim et al, 2008;Kim et al, 2002), via the interference with NF-κB activation. Further studies demonstrate that costunolide has antitumor potential by inhibiting proliferation, inducing apoptosis and reducing invasion and metastasis of a wide variety of tumor cells, including breast cancer cells (Bocca et al, 2004;Choi et al, 2005;Choi et al, 2011), hepatocellular carcinoma cells (Chen et al, 1995;Liu et al, 2011a;Sun et al, 2003), prostate cancer cells (Hsu et al, 2011), leukemia cells (Choi et al, 2002a;Choi and Lee, 2009;Choi et al, 2002b;Hibasami et al, 2003;Kanno et al, 2008;Kim et al, 2008;Kim et al, 2002;Kim et al, 2011b;Komiya et al, 2004;Lee et al, 2001;Song et al, 2001;Srivastava et al, 2006), gastric cancer cells (Ko et al, 2005;Rasul et al, 2011), colon cancer cells (Kawamori et al, 1995;Mori et al, 1994), melanoma cells (Chen et al, 2007;…”
Section: Biological Functionsmentioning
confidence: 97%
“…Furthermore, costunolide potentiated 1,25-(OH)2D3-induced differentiation in HL-60 promyelocytic leukemia cells (Choi et al, 2002b;Kim et al, 2008;Kim et al, 2002), via the interference with NF-κB activation. Further studies demonstrate that costunolide has antitumor potential by inhibiting proliferation, inducing apoptosis and reducing invasion and metastasis of a wide variety of tumor cells, including breast cancer cells (Bocca et al, 2004;Choi et al, 2005;Choi et al, 2011), hepatocellular carcinoma cells (Chen et al, 1995;Liu et al, 2011a;Sun et al, 2003), prostate cancer cells (Hsu et al, 2011), leukemia cells (Choi et al, 2002a;Choi and Lee, 2009;Choi et al, 2002b;Hibasami et al, 2003;Kanno et al, 2008;Kim et al, 2008;Kim et al, 2002;Kim et al, 2011b;Komiya et al, 2004;Lee et al, 2001;Song et al, 2001;Srivastava et al, 2006), gastric cancer cells (Ko et al, 2005;Rasul et al, 2011), colon cancer cells (Kawamori et al, 1995;Mori et al, 1994), melanoma cells (Chen et al, 2007;Park et al, 2001b), cervical cancer cells (Sun et al, 2003), KB and P388 tumor cell (Mondranondra et al, 1990), and platinum-resistant human ovarian cancer cells . It was also reported that costunolide inhibited angiogenic response by blocking the angiogenic factor signaling pathway (Jeong et al, 2002) and microtubule-interactting activity of costunolide (Bocca et al, 2004).…”
Section: Biological Functionsmentioning
confidence: 98%
“…The anticancer activity in vitro and the pharmacological mechanism of Cos have been reported in many papers (Bocca et al 2004;Choi et al 2002;Jeong et al 2002).…”
Section: Antitumor Potential Of Vosl or Cos-dehy Against Mcf-7 Breastmentioning
confidence: 99%